The Role of the Waste Bank at Islamic Boarding Scholl Darussalam Blokagung in Supporting the Achievement of SDGs Pillars. - Madaniya, Nadiya El; Listyarini, Rakhmawati (Jurnal Internasional Ekonomi Islam, 2024)
Introduction: Sustainable Development (SDGs) is a big agenda compiled by the United Nations, with 17 goals, one of which is reducing waste. The waste problem is currently serious. The more people who are active, the more waste is generated. The solution to handling the waste problem must be good management. One of them is the waste bank program. The waste bank is a program that utilizes sorted waste. The waste bank system is like the bank system, but what is stored is dry waste that can be recycled. Objectives: This study aims to see the role of Islamic boarding in supporting SDG achievement through waste management programs. In addition, the purpose of this study is the impact of a waste bank on the Islamic boarding school environment. Method: This study uses a qualitative approach. The discussion of this research is based on the results of observations and interviews with waste bank management. Results: The results of this study are positive, indicating that the existence of a waste bank at least helps and supports sustainable development and that this waste bank activity provides an example to students of how to manage waste properly and correctly. However, the obstacle is that not all students are aware of this. So, the impact of waste bank activity has been running until now but is not too significant. Implications: To help and contribute to the enforcement of SDGs, this research is expected to have an impact on the management of waste bank management not only for Islamic boarding schools but also for other educational institutions by utilizing the surrounding environment and the students in it.